Analysis Of Working Capital Management On Liquidity And Financial Performance Of Manufacturing Companies - Cahya Susena, Karona; Hidayah , Nenden Restu; Tarigan , Heskyel Pranata (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of working capital management on liquidity and financial performance of manufacturing companies. The number of samples used was 41 companies obtained using purposive sampling method. The research data source used is secondary data in the form of annual financial reports published by the official web www.idnfinancials.com in the 2016-2019 period. The data analysis technique used is panel data analysis and Moderated Regression Analysis (MRA). Based on the results of the study, it shows that working capital management does not have a significant effect on liquidity, profitability as a moderating variable is not able to moderate working capital management on liquidity.